Modeling of the morphometric relations with the production of Araucaria angustifolia (Bertol.) Kuntze IN southern Brazil Modelagem das relações morfométricas com a produção de pinhas de Araucaria angustifolia (Bertol.) Kuntze no sul do Brasil - Atanazio K.A. (2022)
© 2022, Universidade Federal de Santa Maria. All rights reserved.Morphometric relationships refer to the space that a tree needs to develop and they assist in forest management practices. Therefore, this study aimed to fit models between these morphometric relationships and the number of pine cones from Araucaria angustifolia (Bertol.) Kuntze forest sites located in Lages, Bom Jardim da Serra and Painel, in Santa Catarina state. The sampling focused on cone-producing female trees, then it measured the variable circumference at 1.30 meters from the soil surface, total height, number of pine cones, crown insertion height, and four crown rays. Subsequently, the variable diameter at 1.30 meters from the soil surface, canopy length, crown area, canopy ratio, crown diameter, range Index, salience index, slenderness rate, crown formal, and a potential number of trees per hectare for each crown area were calculated. Along with the data set, the descriptive statistics of each variable were calculated and Pearson’s correlation analysis was performed, which made it possible to model the number of pine cones as a function of the morphometric variables with the highest correlation. The residuals of the fitted models were subjected to tests of normality, homogeneity of variances, and interdependence of errors, using generalized linear models. The means of production of cones and of the highest dendro-morphometric variables were found in the forest site of Lages. The independent diameter variables at breast height, crown proportion, crown length and crown diameter showed a correlation of 0.23, 0.15, 0.18, 0.20%, respectively. The model results showed that the number of pine cones is more related to the diameter and crown variables, indicating that forest management should provide lateral space for the good development of crowns because it assists the production of pine cones and the reduction of competition.